Gyrosigma dongtingense sp. nov. (Bacillariophyta) from Dongting Lake, China - Yi, Man-Qi; Liu, Bing; Rioual, Patrick; Lei, Qin; Ma, Yi-Dan (Phytotaxa, 2024)
Dongting Lake is China’s second largest freshwater lake; some new diatom species have been described from this lake recently. The current study describes a new diatom species from this lake, Gyrosigma dongtingense sp. nov. Gyrosigma dongtingense sp. nov. belongs to the section Strigiles sensu H. Peragallo and it is characterized by: 1) its large cell size (valves are 161–218 μm long and 24–29 μm wide), 2) having two curvatures for each half of its raphe sternum, 3) the transverse stria density (12–14 in 10 μm) lower than the longitudinal stria density (16–18 in 10 μm), 4) both the external proximal raphe fissures deflecting towards the convex side of each corresponding half-valve, 5) T-shaped internal proximal raphe fissures, and 6) a prominent axial costa presents along the primary side of the raphe sternum. The isomorphism and dimorphism of the external proximal raphe fissures are reviewed, and similar taxa are discussed.